Electric vehicle market in the national economy (on the materials of presrelizes) - Yelisieieva L, Liudmyla; Pavlova, Olena; Kolosok, Andrii; Suriak, Alla; Strilchuk, Rostyslav; Safarova, Anna; Kozak, Svitlana (MAGNANIMITAS, 2021)
The relevance of the study of the electric car market is due to the high dynamics of the development of supply and demand of electric vehicles in national and international economies. The article aims to study the peculiarities of development and state regulation of the electric car market in Ukraine in foreign experience and generalization of recommendations for optimizing the functioning of such a market in the national economy. A systematic approach was applied, which allowed analyzing the structure of demand and supply of electric vehicles, the nature of competition, and the dynamics of changes in the number of such vehicles in recent years. Comparative analysis was used to compare the level of electric vehicle markets and their institutional support in Ukraine and abroad. The theoretical bases of electric car market research are revealed, particularly the properties of the electric car as an economic good, the main elements of the electric car market. The advantages and disadvantages of electric cars compared to traditional cars are clarified. The factors influencing the development of the electric car market in the global and national economies are systematized. The main tendencies of growth of the world market of electric cars and features of formation of the national market of such vehicles are analyzed. The foreign experience of state regulation of the electric car market and the main ways of development in Ukraine in modern conditions are revealed.
Keywords: Electric car market; Greening of production; Press release; State regulation of the electric car marke; Subjectivity